A general model of temporary aquatic habitat use: Water phenology as a life history filter. Issue 4 (13th June 2019) - Heim, Kurt C.; McMahon, Thomas E.; Calle, Leonardo; Wipfli, Mark S.; Falke, Jeffrey A.
Abstract: Temporary aquatic habitats are not widely appreciated fish habitat. However, fish navigate the transient waters of intertidal zones, floodplains, intermittent and ephemeral streams, lake margins, seasonally frozen lakes and streams, and anthropogenic aquatic habitats across the globe to access important resources. The selective pressures imposed by water impermanence (i.e., freezing, drying, tidal fluctuations), however, operate similarly across taxa and ecosystems. These similarities are formalized into a conceptual model relating habitat use to surface water phenology. Whereas all necessary life history functions (spawning, foraging, refuge, and dispersal) can be accomplished in temporary habitats, the timing, duration, and predictability of water act as a "life history filter" to which habitats can be used and for what purpose. Habitats wet from minutes to months may all be important—albeit in different ways, for different species. If life history needs co‐occur with accessibility, temporary habitats can contribute substantially to individual fitness, overall production and important metapopulation processes. This heuristic is intended to promote research, recognition and conservation of these frequently overlooked habitats that can be disproportionately important relative to their size or brevity of existence. There is a pressing need to quantify how use of temporary aquatic habitats translates to individual fitness benefits, population size and temporal stability, and ecosystem‐level consequences. Temporary aquatic habitats are being impacted at an alarming rate by anthropogenic activities altering their existence, phenology, and connectivity. It is timely that scientists, managers and policymakers consider the role these habitats play in global fish production.